Die kiemdodende effek van ultravioletlig op geïnfekteerde druksere - A. Burger; M.J. Jordaan; G.E. Schoombee (South African Journal of Physiotherapy)
The bactericidal effect of a contact E4 dose of abiotic ultraviolet light on infected pressure sores was investigated. Cultures of swabs taken after irradiation showed a marked reduction in the number of micro-organisms. Most types of micro-organisms were completely destroyed. Where present after irradiation, the numbers were very small.